2017
DOI: 10.3390/bs7030045
|View full text |Cite
|
Sign up to set email alerts
|

Family Communication at the End of Life

Abstract: People often feel awkward and ill at ease when faced with the opportunity for communication at the end of life, thus the overall theme for the articles in this special issue is the creation of more awareness and knowledge regarding the depth, breadth, and importance of current research exploring family communication at the end of life. This introductory essay attempts to accomplish the following: (1) discuss the importance of talk regarding death; (2) highlight the formative role of family interactions on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 33 publications
3
60
0
4
Order By: Relevance
“…Limited communication can result in family conflicts 45 . Communication may help family members to come together and talk about what is on their minds, which often results in less stress 46 . However, it is important to consider each family member's standpoint, as this paper found that family members within the same family often have differing perceptions of family communication.…”
Section: Discussionmentioning
confidence: 92%
“…Limited communication can result in family conflicts 45 . Communication may help family members to come together and talk about what is on their minds, which often results in less stress 46 . However, it is important to consider each family member's standpoint, as this paper found that family members within the same family often have differing perceptions of family communication.…”
Section: Discussionmentioning
confidence: 92%
“…Prior to 2004, scholars exploring familial interactions in the midst of death and dying primarily focused on the perspective of the terminally ill person [ 2 ]. It is only within the last fourteen years that a focus on the “other” person (i.e., family members or close others), through the participation in final conversations, has been explored [ 3 ]. Findings suggest that final conversations have the potential to have a tremendous impact on family relationships (biological, legal, or chosen families) [ 1 , 4 ].…”
Section: Summary Of Final Conversations Researchmentioning
confidence: 99%
“…Final conversations often give terminally ill people the opportunity to help their family members move forward after the death by providing advice, direction and permission to move on, as well as creating a sense of closure and completion of the relationship [ 1 , 2 ]. It is only through communication that terminally ill people and their family members can work together to achieve greater meaning about life, death, and their relationships [ 3 ].…”
Section: Summary Of Final Conversations Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…This presents challenges to the relationships among bereaved family members, who struggle to understand the grief of their relatives (Bosticco & Thompson, 2005; Sedney, Baker, & Gross, 1994). Despite the relational implications of family death, challenges associated with studying bereavement have limited the capacity of past research, which has primarily centered the individual (Bosticco & Thompson, 2005; Keeley, 2017; Traylor, Hayslip, Kaminski, & York, 2003). Though valuable, these studies do not fully capture the interdependence of the family system and are thus unable to comprehend the extent to which individual experiences with loss impact the relationships between surviving family members.…”
mentioning
confidence: 99%